Use of health services by preschool-aged children who are developmentally vulnerable and socioeconomically disadvantaged: testing the inverse care law - Woolfenden, Sue; Galea, Claire; Badland, Hannah; Smithers Sheedy, Hayley; Williams, Katrina; Kavanagh, Anne M; Reddihough, Dinah; Goldfeld, Sharon; Lingam, Raghu; Badawi, Nadia; O'Connor, Meredith (My University, 2020)
The inverse care law suggests that those with the greatest need for services are least likely to receive them. Our aim of this study was to test the inverse care law in relation to the use of health services by children aged 4-5 years in Australia who were developmentally vulnerable and socioeconomically disadvantaged. Cross-sectional data were collected from the Longitudinal Study of Australian Children birth cohort when the children were aged 4-5 years. Children were grouped according to the combination of developmental vulnerability (yes, no) and socioeconomic disadvantage (lower, higher), resulting in four groups (reference group: developmentally vulnerable and disadvantaged). Multivariate regression was used to examine the impact of the combination of developmental vulnerability and disadvantage on health service use, adjusting for other sociodemographic characteristics. 3967 (90%) of children had data on developmental vulnerability at 4-5 years. A third of children (32.6%) were classified as developmentally vulnerable, and 10%-25% of these children had used health services. Non-disadvantaged children who were developmentally vulnerable (middle need) had 1.4-2.0 times greater odds of using primary healthcare, specialist and hospital services; and non-disadvantaged children who were not developmentally vulnerable (lowest need) had 1.6-1.8 times greater odds of using primary healthcare services, compared with children who were developmentally vulnerable and disadvantaged (highest need). We found some evidence of the inverse care law. Equity in service delivery remains a challenge that is critically important to tackle in ensuring a healthy start for children.
Keywords: child health; disability; paediatric; social inequalities; Disadvantage, adversity and resilience; Childhood and child development; Health and wellbeing